ANALISIS PERUBAHAN PENGGUNAAN LAHAN DI KECAMATAN MOJOSONGO KABUPATEN BOYOLALI AKIBAT PEMBANGUNAN GERBANG TOL BOYOLALI - Hanin Khoirunnisa; Pipit Wijayanti; Rahning Utomowati (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2023)
Boyolali is one of the districts in the Central Java province that is often passed when the flow of mudik or vacation. The existence of a toll gate in the region prompted the occurrence of land use changes in the area around the Boyolali toll gate. The change in land use in the Mojosongo district from 2011 to 2018 was dominated by the change from the use of land to the fields of 58,17 Ha and the change of the farm to settlements with an area of 78,88 Ha. The research method used is quantitative. The approach used is descriptive. Subsequently, the data collection used is an observation technique for testing the validity of image changes in land use and interpretation of image to find land use changes in the Mojosongo district. The result of this study is the change in land use that occurred in the district of Mojosongo and which was quite large in 2011 to 2018 that is, the transfer of land use function from agriculture to non-agriculture and the change of land function 2018 to 2022 occurred not so significant only the addition of the settlement area but not in the entire district.